The Physical-Biogeochemical Responses to a Subsurface Anticyclonic Eddy in the Northwest Pacific - Ding, Ya-nan; Yu, Fei; Ren, Qiang; Nan, Feng; Wang, Ran; Liu, Yansong; Tang, Ying (Frontiers in Marine Science, 2022)
Due to the unique physical processes of mesoscale eddies, the physical and biogeochemical properties within the subsurface anticyclonic eddy (SSAE) and in the surrounding water are distinct. Analyses using satellite and model data have revealed distinct seasonal variations in the central potential density structure of a long-standing SSAE south of Japan; this SSAE exhibits a normal concave isopycnals structure from January to April and a convex lens isopycnals structure from May to December, and these variations may be related to the subduction of low-potential vorticity (PV) mode water. In contrast to the idea of the self-sustained oscillation mechanism, the strength of the SSAE was enhanced due to the eddy kinetic energy provided by dramatic increasing of the positive baroclinic conversion rate during the Kuroshio path transition period from the non-large meander (NLM) path to the large meander (LM) path. Twofold to threefold enhancement of chlorophyll (CHL) was detected in the subsurface CHL maximum layers at the core of the SSAE, and this enhancement was related to the injection of nutrients into the euphotic layer due to winter mixing and the convex of isopycnals. During the period from May to December, elevated CHL and dissolved oxygen (DO) levels and reduced nitrate levels were observed along the periphery of the eddy below the maximum subsurface CHL anomaly depth. The combined result of these two processes: (1) the central downward displaced isopycnals caused by intensified SSAE, and (2) winter mixing deepened to the nutricline due to the thickened mixed layer depth (MLD) and weakened stratification in winter 2017 (during the NLM period) may have led to numerous nutrients and CHL enrichments throughout the mixed layer, thus generating a CHL bloom in the following April. The SSAE intensified in winter 2018 (during the LM period), whereas the shallower MLD and stronger stratification limited the depth of CHL downward displacement.